Values of Ukrainian Musical Folklore in the Process of TRAININg of Future Music Teacher - Galyna Yakivchuk; Lyudmyla Vroda (Pedagogical Discourse, 2013)
The article considers the value of Ukrainian folk music and its impact on the education of future teachers of music. The author analyzed and emphasized the importance of opportunities basic values folklore (historical, philosophical, educational, moral, aesthetic, creative). The article grounded internal educational opportunities and values inherent in Ukrainian folk music to help vdosyahnenni tasks of modern higher education to educate the person who owns the new thinking, deeply aware of the unity and interdependence of the world, the ability to live in harmony with yourself creatively use the value potential of folk music in educational practice.